Tongkat Ali (Eurycoma longifolia): a possible therapeutic candidate against Blastocystis sp. - Sonal Girish; Suresh Kumar; Norhaniza Aminudin (Parasites & Vectors, 2015)
Abstract Background In the local Malaysian context, herbal plants such as Eurycoma longifolia (Tongkat Ali), Orthosiphon stamineus (MisaiKucing), Ficus deltoidea (Mas Cotek), Zingiber officinale (Halia Bara) and Barringtonia racemosa (Putat) are known and widely used for its therapeutic properties. The first part of this study aims to screen for the anti-protozoal activity of these herbal plant extracts against Blastocystis sp. isolate subtype (ST) 3. Herbal extract with the highest efficacy was further fractionized into water and ethyl acetate fractions and tested against ST1, ST3 and ST5 Blastocystis sp. isolates. These isolates were also exposed to allopathic drugs, Metronidazole (MTZ), Tinidazole, Trimethoprim-sulfamethoxazole(TMP-SMX), Ketoconazole and Nitazoxanide for comparison purpose. Methods Blastocystis sp. isolates from human-derived stool samples were exposed to herbal extracts and allopathic drugs at a concentration of 0.1 mg/ml and 1.0 mg/ml and were incubated at 37 °C. Growth profile studies were carried out. After 72 h of treatment, the viability of Blastocystis sp. as a result of the effects of the drugs and herbal extracts were assessed. Results Based on the screening process, amongst all the extracts, Tongkat Ali exhibited the highest anti-protozoal activity at 1.0 mg/ml. Between the water and ethyl acetate fractions of Tongkat Ali, the ethyl acetate fraction exhibited a slightly higher percentage of anti-protozoal activity at 1.0 mg/ml across subtypes, ST1 (94.9 %), ST3 (95.1 %) and ST5 (94.3 %). When tested with allopathic drugs, at the same concentration, MTZ exhibited the highest anti-protozoal activity across subtypes, ST1 (95.8 %), ST3 (93.4 %) and ST5 (90.8 %). Conclusion This study is the first to describe the anti-protozoal properties of Tongkat Ali against Blastocystis sp. isolates. Ethyl acetate fraction of Tongkat Ali demonstrated the highest anti-protozoal activity against Blastocystis sp. isolates and showed a sizeable reduction in the cell count which was comparable with MTZ. Tongkat Ali also demonstrated a more uniformed sensitivity across subtypes in comparison to the allopathic drugs.